Algorithms and Employment: A Review of AI’s Impact on the Labour Market - Maria Alexandra CRACIUN; Irina Carmen BĂLUȚ GABOROI (Management and Economics Review)
This paper investigates the economic implications of Artificial Intelligence (AI) on the global labour market through a systematic literature review of highly cited literature published within the past decade – a period characterised by significant scholarly attention to AI’s development and its economic consequences. By examining labour market dynamics, this study synthesises existing research to address the central question: How does AI impact labour markets on a global scale? The employed methodology enabled the identification of key themes, including the transformation of employment structures, evolving skill requirements, and automation’s differential effects across occupational categories and geographic regions. This paper contributes to the scholarly discourse by offering a comprehensive synthesis of empirical findings and theoretical frameworks concerning AI’s economic ramifications. The analysis reveals future research trajectories and underscores the imperative for evidence-based policy interventions designed to maximise AI’s socioeconomic benefits while mitigating potential labour market disruptions. The findings have significant implications for policymakers, industry stakeholders and educational institutions as they navigate the complexities of this technological progress in the labour markets.